Solitary living in Alzheimer’s disease over 3 years: association between cognitive and functional impairment and community-based services - Wattmo C (Dove Medical Press, 2014)
Carina Wattmo, Elisabet Londos, Lennart Minthon Clinical Memory Research Unit, Department of Clinical Sciences, Malmö, Lund University, Malmö, SwedenIntroduction: Many individuals with Alzheimer’s disease (AD) live alone, and this figure is expected to increase. This study aimed to describe the cognitive and functional abilities of solitary-living AD patients, and the potential predictors of their usage of community-based services.Methods: This 3-year, prospective, multicenter study included 1,021 participants with mild-to-moderate AD (Mini-Mental State Examination score, 10–26) treated with a cholinesterase inhibitor in a routine clinical setting. At baseline and every 6 months, patients were assessed using cognitive, instrumental, and basic activities of daily living (ADL) scales, and service utilization was recorded. Logistic regression models were used to predict the usage of community-based services.Results: At the start of cholinesterase inhibitor therapy (time of AD diagnosis), 355 individuals (35%) were living alone. They were mainly female, older, had more impaired basic ADL capacity, and had a larger number of concomitant medications when compared with those living with family. Regarding the solitary-living patients, lower instrumental ADL (IADL) ability and more medications were independent predictors of usage of home-help services, whereas more impaired IADL at baseline and faster IADL deterioration were predictors of nursing home admission. For those living with family, older age, lower basic ADL, and a greater number of medications predicted home-help services, whereas a larger amount of home help predicted nursing home placement. In addition, female sex was a risk factor for both the utilization of home-help services and nursing home placement. Cognitive ability was not significantly associated with the usage of community-based services.Conclusion: A large number of AD patients, predominantly females, live alone with severe cognitive and functional impairment. The amount of home-help services used did not reflect cognitive severity, suggesting that home help did not meet the needs related to cognitive deterioration. Increased knowledge of how community-based services can better accommodate the care needs of solitary-living individuals with AD is essential.Keywords: cognition, activities of daily living, living status, home-help services, nursing home placement, longitudinal study